PEMANFAATAN MOBILE GAMES DALAM PEMBELAJARAN MATEMATIKA UNTUK MENINGKATKAN PEMAHAMAN KONSEP PERKALIAN PADA SISWA SEKOLAH DASAR: STUDI LITERATUR - Fadiyah Nadhifah; Dian Anggeraini Maharbid (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Multiplication is one of the fundamental mathematical concepts that elementary school students must master as a foundation for learning more complex mathematical topics. However, many students still experience difficulties in understanding multiplication concepts due to teacher-centered learning approaches and the limited use of interactive learning media. The rapid development of digital technology has created opportunities for utilizing mobile games as learning media that can enhance students' motivation and engagement. This study aims to analyze the utilization of mobile games in mathematics learning to improve elementary school students' understanding of multiplication concepts. The research employed a literature review method using a Systematic Literature Review (SLR) approach. Articles were collected from various scientific databases and selected based on their relevance to digital game-based mathematics learning, with publication years ranging from 2020 to 2025. The findings indicate that the use of mobile games and educational games has a positive impact on students' understanding of mathematical concepts, learning motivation, engagement, and academic achievement. Mobile games provide a more interactive learning experience through repetitive practice, immediate feedback, and challenges that align with the characteristics of elementary school students. Therefore, mobile games have the potential to serve as an effective alternative learning medium for improving elementary school students' understanding of multiplication concepts.